Particle, and method for producing particle
By adding a specific fatty acid or aliphatic alcohol component to the production of (meth)acrylic copolymer particles, the challenges of high viscosity and particle size are addressed, resulting in improved mold release and appearance in molded materials.
Patent Information
- Application Number
- JP2023163556
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-08
AI Technical Summary
Existing methods for producing (meth)acrylic copolymers face challenges such as high viscosity of polymerizable droplets, resulting in large particle sizes and coarse particles, and the introduction of silica in suspension polymerization methods, which causes cloudiness in molded materials.
Incorporating a specific component (B), such as a fatty acid, fatty acid derivative, or aliphatic alcohol, with an alkyl chain of 12 to 18 carbon atoms, into the production of (meth)acrylic copolymer particles to improve dispersion stability and control particle size, thereby enhancing mold release and appearance in molded materials.
The approach results in particles with improved dispersion stability and smaller particle sizes, leading to excellent mold release properties and appearance in molded materials, while avoiding the cloudiness associated with silica-containing particles.
Smart Images

Figure 2025054493000001 
Figure 2025054493000002 
Figure 2025054493000003
Abstract
Description
[Technical field]
[0001] The present invention relates to particles and methods for making particles. [Background technology]
[0002] Acrylic resins have excellent transparency, weather resistance, high elasticity, surface hardness, etc., and are therefore widely used in a variety of applications, including display front panels for LCD and OLED, signs, lighting supplies, toys, containers, home appliances, vehicle parts such as interior and exterior parts for vehicles, medical components, industrial materials, construction materials, lenses, light guide plates, light collecting components, and optical components such as the optical films used in LCD and OLED displays. In some of these applications, it is required to impart flexibility and impact resistance to acrylic resin products, and there is also a demand for acrylic resins with excellent melt moldability that allows the acrylic resins to be molded into thin or complex shapes using melt molding methods such as injection molding and extrusion molding.
[0003] As a technique for improving the impact resistance of acrylic resin, for example, Patent Document 1 discloses a resin composition in which a rubber (core-shell rubber) having a core-shell structure, which has a core part made of crosslinked rubber and a shell part that ensures compatibility and dispersibility with the (meth)acrylic polymer that serves as a matrix, is blended with a (meth)acrylic resin. However, the resin composition described in Patent Document 1 has a problem in that the melt viscosity increases due to the inclusion of the core-shell rubber, and the melt moldability tends to decrease, so that the use of the resin composition is limited to resin products with a large thickness or a simple shape.
[0004] As a technique for improving the melt moldability of acrylic resins, resin compositions in which block copolymers and / or graft copolymers are blended with (meth)acrylic resins are known. Block copolymers and / or graft copolymers are composed of two or more polymer segments linked together by chemical bonds, and therefore the phase separation structure of a resin composition in which a block copolymer and / or graft copolymer having a poly(meth)acrylate chain is blended with an acrylic resin is nanometer-sized (called a "microphase separation structure"). Therefore, in such a resin composition and a molded product obtained by molding the resin composition, it is possible to express the properties of both the acrylic resin as the matrix and the block copolymer and / or graft copolymer, and further, it is possible to express the properties of each polymer segment of the block copolymer and / or graft copolymer.
[0005] As a method for producing the block copolymer and / or graft copolymer, there is a method for obtaining the copolymer as particles by a suspension polymerization method. The suspension polymerization method is superior to other polymerization methods such as emulsion polymerization and bulk polymerization in that the heat generated by polymerization can be easily controlled and impurities can be removed by washing the particles. On the other hand, it is important to optimize the particle size of the resulting particles in order to improve the polymerization stability at the manufacturing site, the passability in post-processing such as washing and drying, the handleability of the resulting particles, and the quality of the product. However, when producing block copolymers and / or graft copolymers, it is necessary to synthesize each polymer chain sequentially, and a long time passes during the polymerization reaction in a highly viscous state in which the polymer and monomer coexist. Therefore, there was a concern that it would be difficult to control the dispersion stability and particle size in the suspension polymerization method.
[0006] For example, Patent Document 2 discloses that a (meth)acrylate monomer is added to an aqueous suspension of a (poly)methacrylate copolymer to obtain a bead-like block copolymer and / or a graft copolymer. Furthermore, Patent Documents 3 and 4 disclose a method of performing suspension polymerization in the presence of colloidal silica and an alkali metal halide as a method of improving the dispersion stability of oil droplets in a suspension polymerization system, homogenizing the particle size distribution, and reducing the particle size. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 62-21804 [Patent Document 2] Patent Publication No. 2022-65185 [Patent Document 3] JP 2007-217645 A [Patent Document 4] JP 2015-193861 A Summary of the Invention [Problem to be solved by the invention]
[0008] The method described in Patent Document 2 has a problem in that the viscosity of droplets made of a polymerizable component is high, so that the average particle size of the obtained particles is large and coarse particles are easily generated. Furthermore, in the methods described in Patent Documents 3 and 4, the particles obtained contain silica, and so when these particles are kneaded with another resin to produce a molding material, the molded article produced using the molding material becomes cloudy, which is a problem.
[0009] The present invention aims to solve the problems of the conventional technology described above, and to provide particles of a (meth)acrylic copolymer, which have high dispersion stability of droplets during a polymerization reaction and can be made into particles having a smaller particle size, and which can provide a molding material containing the particles and a molded article obtained by molding the molding material with excellent releasability and appearance, and a method for producing the same. [Means for solving the problem]
[0010] As a result of extensive investigations aimed at solving the above problems, the present inventors have found that the above problems can be solved by adding a specific component (B) during the production of particles of the (meth)acrylic copolymer (A). That is, the present invention relates to the following.
[0011] [1] A particle comprising a (meth)acrylic copolymer (A) and a component (B), the (meth)acrylic copolymer (A) is a block copolymer and / or a graft copolymer, The particle, wherein the component (B) is at least one selected from a fatty acid, a fatty acid derivative, and an aliphatic alcohol.
[0012] [2] The particles according to [1], wherein the component (B) has an alkyl chain having 12 to 18 carbon atoms.
[0013] [3] The particles according to [1] or [2], wherein the component (B) contains an aliphatic alcohol.
[0014] [4] The particles according to any one of [1] to [3], wherein the content of the component (B) is 0.0001 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the (meth)acrylic copolymer (A).
[0015] [5] The particles according to any one of [1] to [4], wherein the (meth)acrylic copolymer (A) contains a polymer (A1) containing 50 mass % or more of repeating units derived from methyl methacrylate in the polymer molecule.
[0016] [6] The particles according to any one of [1] to [5], wherein the volume average particle size of the particles is 30 μm or more and 600 μm or less.
[0017] [7] Particles according to any one of [1] to [6], wherein the proportion of coarse particles remaining on a sieve having an opening of 1,400 μm among the particles is 30 mass% or less.
[0018] [8] The particles according to any one of [5] to [7], wherein the (meth)acrylic copolymer (A) is a polymer containing the polymer (A1) and the polymer (A2) in the polymer molecule, and the polymer (A2) has a glass transition temperature (Tg) of 0°C or lower.
[0019] [9] The particle according to any one of [5] to [8], wherein the (meth)acrylic copolymer (A) contains, as the polymer (A1), a structural unit derived from a macromonomer (a1) represented by the following general formula (1):
[0020] [ka]
[0021] (In formula (1), R 0 ~R n are each independently a hydrogen atom, an alkyl group, a cycloalkyl group, an aryl group, or a heterocyclic group. 1 ~X n are each independently a hydrogen atom or a methyl group. Z is a terminal group. n is a natural number from 1 to 10,000.
[0022]
[10] The particles according to [8] or [9], wherein the monomer units constituting the polymer (A2) are structural units derived from one or more monomers (a2) selected from the group consisting of methyl acrylate, ethyl acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tridecyl (meth)acrylate, i-stearyl (meth)acrylate, and styrene.
[0023]
[11] A method for producing particles, comprising a step of polymerizing a mixture containing a polymerizable composition (X), a component (B), and a polymerization initiator, the polymerizable composition (X) contains a macromonomer (a1) and a monomer (a2) copolymerizable with the macromonomer (a1); The method for producing particles, wherein the component (B) is at least one selected from the group consisting of fatty acids, fatty acid derivatives, and aliphatic alcohols.
[0024]
[12] The method for producing particles according to
[11] , wherein the particles have a volume average particle size of 30 μm or more and 600 μm or less.
[0025]
[13] The method for producing particles according to
[11] or
[12] , wherein the component (B) contains an alkyl chain having 12 to 18 carbon atoms.
[0026]
[14] The method for producing particles according to any one of
[11] to
[13] , wherein the component (B) contains an aliphatic alcohol.
[0027]
[15] The method for producing particles according to any one of
[11] to
[14] , wherein the macromonomer (a1) is represented by the following formula (1):
[0028] [ka]
[0029] (In formula (1), R 0 ~R n are each independently a hydrogen atom, an alkyl group, a cycloalkyl group, an aryl group, or a heterocyclic group. 1 ~X n are each independently a hydrogen atom or a methyl group. Z is a terminal group. n is a natural number from 1 to 10,000.
[0030]
[16] The method for producing particles according to
[15] , wherein the monomer (a2) is one or more selected from the group consisting of methyl acrylate, ethyl acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tridecyl (meth)acrylate, i-stearyl (meth)acrylate, and styrene. Effect of the Invention
[0031] The particles of the present invention contain at least one selected from the group consisting of fatty acids, fatty acid derivatives, and aliphatic alcohols as component (B), and thus the dispersion stability of the droplets during the polymerization reaction is improved, and the particles can be produced as particles having a smaller particle size. Furthermore, the molding material containing the particles of the present invention and the molded article obtained by molding the molding material have excellent mold releasability and appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Hereinafter, the embodiments of the present invention will be described in detail, however, the present invention is not limited to the following description and can be modified in various ways within the scope of the gist of the present invention. In the present invention, "(meth)acrylic" means one or both of "acrylic" and "methacrylic". In addition, "(meth)acrylate" means one or both of "methacrylate" and "acrylate". The same applies to "(meth)acryloyl".
[0033] In the present invention, "monomer" means an unpolymerized compound (monomer component before polymerization), and "repeating unit" and "structural unit" mean a structural unit constituting a polymer derived from a monomer formed by polymerization of the monomer. Furthermore, a structural unit constituting a polymer is referred to as a "monomer unit". A "repeating unit" or a "structural unit" may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. In the present invention, "mass %" indicates the content of a specific component contained in a total amount of 100 mass %. In the present invention, unless otherwise specified, a numerical range expressed using "to" in this specification means a range including the numerical values written before and after "to" as the lower and upper limits, and "A to B" means A or more and B or less.
[0034] In the present invention, the mass average molecular weight (Mw) of the (meth)acrylic copolymer (A) means a mass average molecular weight which is a relative molecular weight determined using gel permeation chromatography (GPC) and converted into polymethyl methacrylate (PMMA).
[0035] [particle] The particles of the present invention contain, as essential components, a (meth)acrylic copolymer (A) which is a block copolymer and / or a graft copolymer, and a component (B) described below. The (meth)acrylic copolymer (A) is preferably a polymer containing a polymer (A1) and a polymer (A2) described below in the polymer molecule.
[0036] <Volume average particle size of particles> The lower limit of the volume average particle diameter of the particles of the present invention is preferably 10 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, particularly preferably 100 μm or more, and most preferably 150 μm or more. If the volume average particle diameter is 10 μm or more, the particles have good fluidity and handleability. The upper limit of the volume average particle diameter of the particles of the present invention is preferably 1,400 μm or less, more preferably 720 μm or less, even more preferably 700 μm or less, particularly preferably 600 μm or less, and most preferably 500 μm or less. If the volume average particle diameter is 1,400 μm or less, the particles can be easily washed, dehydrated, dried, etc. The above preferred upper and lower limits can be combined in any manner. The volume average particle size of the particles is a value measured by the method described in the Examples section below.
[0037] <Coarse particles contained in particles> The term "coarse particles" refers to particles that remain on a sieve containing the obtained particles and that are present when the particles are sieved using a sieve with an opening of 1,400 μm. The particles of the present invention contain the component (B) used in the production thereof, so that the particles have a fine particle size and the formation of coarse particles is suppressed. Therefore, the proportion of coarse particles in the particles of the present invention is preferably 30% by mass or less, and the lower this proportion, the more preferable, and it may be 0% by mass, that is, no coarse particles may be present.
[0038] [(Meth)acrylic copolymer (A)] The particles of the present invention contain a (meth)acrylic copolymer (A). The (meth)acrylic copolymer (A) is a block copolymer and / or a graft copolymer, that is, the (meth)acrylic copolymer (A) has at least one of the structure of a block copolymer and a graft copolymer.
[0039] The block and / or graft structure of the (meth)acrylic copolymer (A) according to the present invention may be any of diblock, triblock, multiblock, graft, cyclic, star, comb, dendritic, ladder, etc., or may be a combination of a plurality of these structures. Among these structures, it is preferable to have at least one of the diblock, triblock, and graft structures, since they can impart excellent impact resistance and flexibility and are relatively easy to produce.
[0040] The (meth)acrylic copolymer (A) according to the present invention may contain a polymer (A1) and a polymer (A2) described below in the polymer molecule, and preferably contains a polymer (A1) and a polymer (A2). In this case, for example, the (meth)acrylic copolymer (A) may be a graft copolymer in which the main chain is constituted by the polymer (A1) and a graft chain made of the polymer (A2) is branched and connected to the main chain made of the polymer (A1). Conversely, the main chain may be the polymer (A2) and the side chain may be (A1). The (meth)acrylic copolymer (A) may be a block copolymer in which a polymer made of the polymer (A1) and a polymer made of the polymer (A2) are connected in series. Furthermore, the main chain and / or the side chain of the graft copolymer may have a structure containing a block copolymer.
[0041] In the (meth)acrylic copolymer (A), the polymer (A1) has a function of imparting miscibility and compatibility when the particles of the present invention containing the (meth)acrylic polymer (A) are used as a modifier for a matrix resin, and a function of enabling the particles of the present invention containing the (meth)acrylic copolymer (A) to be handled as a solid. In the (meth)acrylic copolymer (A), the polymer (A2) has a function of imparting flexibility, impact resistance, moldability, etc.
[0042] The matrix resin to which the particles of the present invention are applied is not particularly limited, but examples thereof include the following thermoplastic resins (1) to (3). (1) General-purpose resins such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, polytetrafluoroethylene, acrylonitrile butadiene styrene resin, acrylonitrile styrene resin, and acrylic resin ((meth)acrylic resin). (2) Engineering plastics such as polyamides, polyacetals, polycarbonates (e.g., isosorbite-based polycarbonate resins), modified polyphenylene ethers, polyesters, and cyclic polyolefins. (3) Super engineering plastics such as polyphenylene sulfide, polytetrafluoroethylene, polysulfane, polyethersulfane, amorphous polyarylate, liquid crystal polymer, polyetherketone, thermoplastic polyimide, and polyamideimide.
[0043] These can be used alone or in combination of two or more.
[0044] Among these, acrylic resins, polycarbonates, and polyvinyl chloride are preferred because they allow the modifying effect of the (meth)acrylic copolymer (A) to be effectively exerted.
[0045] The lower limit of the weight average molecular weight (Mw) of the (meth)acrylic polymer (A) in terms of PMMA is preferably 50,000 or more, more preferably 100,000 or more, even more preferably 300,000 or more, and particularly preferably 600,000 or more. If the lower limit of the Mw of the (meth)acrylic polymer (A) is 50,000 or more, the performance of the (meth)acrylic copolymer (A) such as heat resistance, hardness, scratch resistance, weather resistance, and transparency is easily exhibited. In addition, the upper limit of the Mw of the (meth)acrylic polymer (A) is preferably 2,500,000 or less, more preferably 2,000,000 or less, and even more preferably 1,500,000 or less. If the upper limit of the Mw of the (meth)acrylic polymer (A) is 2,500,000 or less, the melt viscosity is within an appropriate range, and the melt kneadability and processability are good.
[0046] [Polymer (A1)] The polymer (A1) preferably contains 50% by mass or more and 100% by mass or less of repeating units derived from methyl methacrylate (hereinafter, sometimes referred to as "methyl methacrylate units"), relative to 100% by mass of the total weight of the polymer (A1). The polymer (A1) more preferably contains 80% by mass or more of methyl methacrylate units, further preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on 100% by mass of the total weight of the polymer (A1). If the lower limit of the content of the methyl methacrylate unit in the polymer (A1) is 50% by mass or more relative to 100% by mass of the total weight of the polymer (A1), the polymer (A1) has good affinity with the matrix resin, and has good miscibility and compatibility. On the other hand, the upper limit of the content of the methyl methacrylate unit is not particularly limited as long as it is 100% by mass or less, and the polymer (A1) may be a homopolymer of 100% by mass of the methyl methacrylate unit.
[0047] In addition to the methyl methacrylate units, the polymer (A1) may contain units derived from other comonomers copolymerizable with methyl methacrylate (hereinafter, sometimes referred to as "comonomer units") depending on the purpose. For example, when the polymer (A1) contains an acrylate unit as a comonomer unit, depolymerization of the polymer (A1) when exposed to high temperature conditions such as melt molding can be suppressed, and thermal decomposition resistance can be improved. In addition, by adjusting the type and content of the comonomer unit, the functions of the polymer (A1), such as the glass transition temperature (Tg), processability, heat resistance, refractive index, weather resistance, releasability, and thermal decomposition resistance, can be controlled.
[0048] The upper limit of the content of the comonomer unit in the polymer (A1) is preferably 50% by mass or less relative to the total mass (100% by mass) of the polymer (A1) in order to maintain good performance such as heat resistance, hardness, scratch resistance, weather resistance, transparency, processability, etc. On the other hand, the lower limit of the content of the comonomer unit may be 0% by mass.
[0049] Examples of the comonomers forming the comonomer units of the polymer (A1) include the following a) to i). a) (meth)acrylate ester monomers other than methyl methacrylate, such as methyl acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-lauryl (meth)acrylate, n-stearyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, isobornyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, and phenoxyethyl (meth)acrylate. b) Hydroxyl group-containing (meth)acrylate monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and glycerol (meth)acrylate. c) Carboxyl group-containing vinyl monomers such as (meth)acrylic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxypropyl phthalic acid, 2-(meth)acryloyloxyethyl maleic acid, 2-(meth)acryloyloxypropyl maleic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxypropyl succinic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, monomethyl maleate, and monomethyl itaconate. d) Vinyl monomers containing an acid anhydride group, such as maleic anhydride and itaconic anhydride. e) Epoxy group-containing vinyl monomers such as glycidyl (meth)acrylate, glycidyl α-ethyl acrylate, and 3,4-epoxybutyl (meth)acrylate. f) Amino group-containing (meth)acrylate vinyl monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate. g) Vinyl monomers containing an amide group, such as (meth)acrylamide, Nt-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, diacetone acrylamide, maleic acid amide, and maleimide. h) Vinyl monomers such as styrene, α-methylstyrene, vinyltoluene, (meth)acrylonitrile, vinyl chloride, vinyl acetate, and vinyl propionate i) Polyfunctional vinyl monomers such as divinylbenzene, ethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, allyl (meth)acrylate, and N,N'-methylenebis(meth)acrylamide.
[0050] These can be used alone or in combination of two or more.
[0051] Among these, in terms of easy availability of the monomer, methyl acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, with methyl acrylate being more preferred.
[0052] The polymer (A1) preferably contains a structural unit derived from a macromonomer (a1) described below. In this case, the methyl methacrylate unit may be contained in the macromonomer (a1).
[0053] The polymer (A1) has a PMMA-equivalent weight average molecular weight (Mw) of preferably 5,000 to 100,000, more preferably 10,000 to 70,000, and even more preferably 15,000 to 50,000. If the lower limit of Mw of the polymer (A1) is 5,000 or more, the (meth)acrylic copolymer (A) is more likely to exhibit the properties of heat resistance, hardness, scratch resistance, weather resistance, transparency, and the like. If the upper limit of Mw of the polymer (A1) is 100,000 or less, the melt viscosity is within an appropriate range, and melt-kneadability and processability are improved.
[0054] The polymer (A1) in the present invention may be a mixture of two or more polymers. In that case, the mass average molecular weight Mw is calculated as the value of the entire polymer (A1). When multiple types of polymers (A1) with different mass average molecular weights (Mw) are used in combination, the polymer (A1) with a lower molecular weight plays a role in reducing the syrup viscosity and preventing the copolymer from crosslinking, while the polymer (A1) with a higher molecular weight plays a role in ensuring compatibility with the matrix resin when used as an additive.
[0055] The content of the polymer (A1) contained in the (meth)acrylic copolymer (A) is preferably 35% by mass or more and 75% by mass or less, based on 100% by mass of the total weight of the (meth)acrylic copolymer (A). If the lower limit of the content of the polymer (A1) is 35% by mass or more, it is easy to obtain a particle containing the (meth)acrylic copolymer (A) having excellent miscibility and compatibility with the matrix resin. The lower limit of the content of the polymer (A1) is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 50% by mass or more. On the other hand, if the upper limit of the content of the polymer (A1) is 75% by mass or less, it is easy to obtain the effect of imparting flexibility by the polymer (A2). The upper limit of the content of the polymer (A1) is preferably 70% by mass or less, more preferably 65% by mass or less.
[0056] [Polymer (A2)] The polymer (A2) imparts functions such as flexibility, impact resistance, and improved flowability during melt molding to the particles of the present invention containing the (meth)acrylic copolymer (A) and the resin composition, molding material, and molded article using the same.
[0057] The glass transition temperature (Tg) of the polymer (A2) is preferably 0° C. or lower, more preferably −10° C. or lower, further preferably −20° C. or lower, and particularly preferably −35° C. or lower. When the glass transition temperature (Tg) of the polymer (A2) is 0° C. or lower, effects such as improved flexibility, impact resistance, and flowability during melt molding can be expected. In the present invention, the Tg of the polymer (A2) can be calculated by using the Fox formula, using the numerical value described in a known document such as the Polymer Handbook (POLYMER HANDBOOK FOURTH EDITION 2003) as the Tg of a homopolymer of a monomer that is a constituent unit of the polymer (A2). Alternatively, the dynamic viscoelasticity of the obtained molded article can be measured, and the value of tan δ can be used as the Tg.
[0058] The content of the polymer (A2) contained in the (meth)acrylic copolymer (A) is preferably 25% by mass or more and 65% by mass or less, based on the total weight of the (meth)acrylic copolymer (A) being 100% by mass. If the lower limit of the content of the polymer (A2) is 25% by mass or more, the (meth)acrylic copolymer (A) is more likely to provide the effect of improving flexibility, impact resistance, and moldability. The lower limit of the content of the polymer (A2) is preferably 25% by mass or more, more preferably 30% by mass or more, and even more preferably 35% by mass or more. On the other hand, if the upper limit of the content of the polymer (A2) is 65% by mass or less, the particles of the present invention containing the (meth)acrylic copolymer (A) are easy to handle. The upper limit of the content of the polymer (A2) is preferably 65% by mass or less, more preferably 60% by mass or less, even more preferably 55% by mass or less, particularly preferably 50% by mass or less, and most preferably 45% by mass or less.
[0059] The polymer (A2) preferably comprises a repeating unit derived from the monomer (a2) shown below, which is obtained from the monomer (a2) as a raw material.
[0060] [Monomer (a2)] Monomer (a2) is a monomer used as a raw material for polymer (A2), and is preferably a component copolymerizable with macromonomer (a1) described below. Monomer (a2) is not particularly limited as long as it can produce (meth)acrylic copolymer (A), and various polymerizable monomers can be used as needed. Specifically, it is preferable to mainly use acrylates and aromatic vinyls in terms of setting the glass transition temperature (Tg) low to impart flexibility, impact resistance, and moldability, and in terms of adjusting the refractive index. In addition, other monomers can be used as needed.
[0061] The acrylate used in the monomer (a2) is preferably 70% by mass or more, more preferably 79% by mass or more, and even more preferably 81% by mass or more, based on the total weight of the monomer (a2) being 100% by mass. If the lower limit of the content of the acrylate is 70% by mass or more, the particles of the present invention containing the (meth)acrylic copolymer (A) are provided with the effect of improving flexibility, impact resistance, and moldability. On the other hand, if the content of the acrylate is low, the effect of improving flexibility, impact resistance, and moldability may be insufficient. The upper limit of the content of the acrylate contained in the monomer (a2) is not particularly limited, but is preferably less than 100 mass%, more preferably 95 mass% or less, and even more preferably 90 mass% or less, based on 100 mass% of the total mass of the monomer (a2).
[0062] Moreover, the acrylate can impart superior impact resistance to the resulting molded article, so that the glass transition temperature (Tg) of a homopolymer of the acrylate is preferably lower than 0°C. In the present invention, the Tg of the acrylate homopolymer can be calculated by using the Fox formula and values described in known documents such as POLYMER HANDBOOK FOURTH EDITION 2003.
[0063] Examples of the acrylate used in the monomer (a2) include acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, n-lauryl acrylate, n-stearyl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, isobornyl acrylate, 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, and phenoxyethyl acrylate; hydroxyl group-containing acrylates such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, and glycerol acrylate; 2-acryloyloxyethyl hexahydrophthalic acid, 2-acryloyloxypropyl hexahydrophthalic acid, 2-acryloyloxyethyl phthalic acid, 2-acryloyloxyethyl phthalic acid, and 2-acryloyloxyethyl phthalic acid. Examples of the acrylates include carboxyl group-containing acrylates such as acryloyloxypropyl phthalate, 2-acryloyloxyethyl maleate, 2-acryloyloxypropyl maleate, 2-acryloyloxyethyl succinate, 2-acryloyloxypropyl succinate, etc.; epoxy group-containing acrylates such as glycidyl acrylate, glycidyl α-ethyl acrylate, 3,4-epoxybutyl acrylate, etc.; amino group-containing acrylates such as dimethylaminoethyl acrylate, diethylaminoethyl acrylate, etc.; polyfunctional acrylates such as ethylene glycol diacrylate, 1,3-butylene glycol diacrylate, 1,6-hexanediol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, allyl acrylate, N,N'-methylenebisacrylamide, etc. These can be used alone or in combination of two or more.
[0064] Among the above monomers, 2-ethylhexyl acrylate, 4-hydroxybutyl acrylate, n-butyl acrylate, n-propyl acrylate, ethyl acrylate, and 2-hydroxyethyl acrylate are preferred because the Tg of the homopolymer of the monomer is less than 0° C. Furthermore, methyl acrylate, ethyl acrylate, and n-butyl acrylate are preferred because they are easily available.
[0065] The aromatic vinyl that can be used for the monomer (a2) is used for the purpose of adjusting the refractive index of the polymer (A2) and adjusting the polymerization rate when producing the polymer (A2) and the (meth)acrylic copolymer (A). The content of the aromatic vinyl used in the monomer (a2) is preferably 10 to 30 mass%, more preferably 13 to 21 mass%, and even more preferably 15 to 19 mass%, based on 100 mass% of the total mass of the monomer (a2). When the content of the aromatic vinyl contained in the monomer (a2) is 10 mass% or more, the resin composition, molding material, and molded article containing the particles of the present invention can exhibit good transparency. When the content of the aromatic vinyl contained in the monomer (a2) is 30 mass% or less, the polymerization reaction rate during the production of the (meth)acrylic copolymer (A) becomes sufficiently fast.
[0066] Examples of aromatic vinyls include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, o-ethylstyrene, p-ethylstyrene, pt-butylstyrene, vinylethylbenzene, vinyltoluene, vinylxylene, vinylnaphthalene, diphenylethylene, and divinylbenzene. Among these, styrene is preferred from the viewpoint of practical properties and productivity. These can be used alone or in combination of two or more.
[0067] The monomer (a2) in the present invention may contain other monomers copolymerizable with the acrylate and the aromatic vinyl, if necessary. Examples of other monomers include methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, i-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, n-lauryl methacrylate, n-stearyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, benzyl methacrylate, isobornyl methacrylate, 2-methoxyethyl methacrylate, 2-ethoxyethyl methacrylate, and phenoxyethyl methacrylate; hydroxyl group-containing methacrylates such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, and glycerol methacrylate; 2-methacryloyloxyethyl hexahydrophthalic acid, 2-methacryloyloxypropyl hexahydrophthalic acid, and 2-methacryloyl Carboxy group-containing methacrylates such as oxyethyl phthalate, 2-methacryloyloxypropyl phthalate, 2-methacryloyloxyethyl maleate, 2-methacryloyloxypropyl maleate, 2-methacryloyloxyethyl succinate, and 2-methacryloyloxypropyl succinate; epoxy group-containing methacrylates such as glycidyl methacrylate and 3,4-epoxybutyl methacrylate; amino group-containing methacrylates such as dimethylaminoethyl methacrylate and diethylaminoethyl methacrylate; polyfunctional methacrylates such as ethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, tripropylene glycol dimethacrylate, trimethylolpropane trimethacrylate, and allyl methacrylate; and the like. One or more of these can be appropriately selected and used. Further, examples of other monomers include carboxy group-containing vinyl monomers such as (meth)acrylic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, monomethyl maleate, and monomethyl itaconate; acid anhydride group-containing vinyl monomers such as maleic anhydride and itaconic anhydride; amide group-containing vinyl monomers such as (meth)acrylamide, Nt-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, diacetone acrylamide, maleic acid amide, and maleimide; and vinyl monomers such as (meth)acrylonitrile, vinyl chloride, vinyl acetate, and vinyl propionate. The amount of the other monomers is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, relative to 100% by mass of the total of the monomers (a2), and may not be used.
[0068] From the viewpoints of Tg, availability, and other functionality, the monomer (a2) is preferably at least one selected from the group consisting of methyl acrylate, ethyl acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tridecyl (meth)acrylate, i-stearyl (meth)acrylate, and styrene.
[0069] [Component (B)] Component (B) is added when producing the particles of the present invention, and is an essential component contained in the particles of the present invention. When producing the particles of the present invention, in the polymerization reaction for producing the (meth)acrylic copolymer (A), particularly during suspension polymerization, the affinity of the interface between the oil droplets and the water system is improved, and the coalescence and redispersion of the oil droplets are activated. Due to this effect, it is presumed that the particles of the (meth)acrylic copolymer (A) obtained have a fine particle size, and the formation of coarse particles is suppressed. In addition, the particles of the present invention containing component (B) can impart excellent releasability and appearance to molding materials and molded articles using the particles.
[0070] Examples of component (B) include fatty acids, fatty acid derivatives, and aliphatic alcohols. In particular, from the viewpoint of significantly improving the dispersion stability after redispersion of oil droplets and suppressing the formation of coarse particles, component (B) is preferably one containing an alkyl chain having 12 to 18 carbon atoms, and more preferably one containing an aliphatic alcohol.
[0071] In the particles of the present invention, the content of component (B) is not particularly limited, but is preferably 0.0001 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of (meth)acrylic copolymer (A). The lower limit of the content of component (B) is more preferably 0.0005 parts by mass or more per 100 parts by mass of (meth)acrylic copolymer (A), more preferably 0.001 parts by mass, and particularly preferably 0.002 parts by mass. The upper limit of the content of component (B) is more preferably 0.35 parts by mass, and more preferably 0.2 parts by mass per 100 parts by mass of (meth)acrylic copolymer (A). When the content of component (B) is 0.0001 parts by mass or more relative to 100 parts by mass of (meth)acrylic copolymer (A), the particles of the present invention have a small particle size, and molding materials and molded articles using the particles can exhibit excellent releasability and appearance.When the content of component (B) is 0.5 parts by mass or less relative to 100 parts by mass of (meth)acrylic copolymer (A), the yield of the particles of the present invention is increased, and productivity is improved.
[0072] Specific examples of fatty acids, fatty acid derivatives, and aliphatic alcohols as component (B) are given below. As component (B), one of these may be used alone, or two or more of them may be used in combination.
[0073] <Fatty acids> The number of carbon atoms in the alkyl chain of the fatty acid as component (B) is not particularly limited, but a fatty acid having an alkyl chain with 10 to 25 carbon atoms can be preferably used. The alkyl chain may be either linear or branched, or may be a mixture of linear and branched. Specific examples of fatty acids include saturated fatty acids such as lauric acid, palmitic acid, stearic acid, myristic acid, and behenic acid; unsaturated fatty acids such as oleic acid and linoleic acid; and the like. These fatty acids may be used alone or in combination of two or more. Among these fatty acids, stearic acid, palmitic acid, and myristic acid are preferred, and palmitic acid is more preferred.
[0074] <Fatty acid derivative> The fatty acid derivative as component (B) is not particularly limited, but may be a fatty acid ester derived from a monohydric to octahydric alcohol having an alkyl chain of 1 to 30 carbon atoms and a carboxylic acid having an alkyl chain of 12 to 30 carbon atoms; a fatty acid diamide derived from an alkyl diamine or alkenylene diamine having an alkyl chain of 1 to 6 carbon atoms and a fatty acid having an alkyl chain of 10 to 22 carbon atoms; a fatty acid monoamide derived from an alkyl amine having an alkyl chain of 1 to 22 carbon atoms, an alkenyl amine having an alkyl chain of 1 to 22 carbon atoms, or ammonia and a fatty acid having an alkyl chain of 10 to 22 carbon atoms; etc. The alkyl chain may be either linear or branched, or may be a mixture of linear and branched. These fatty acid derivatives may be used alone or in combination of two or more.
[0075] Examples of the carboxylic acid having an alkyl chain having 12 to 30 carbon atoms include lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, ricinoleic acid, arachic acid, and behenic acid.
[0076] Among the monohydric to octahydric alcohols having an alkyl chain with 1 to 30 carbon atoms, examples of the monohydric alcohol include methanol, ethanol, propanol, butanol, hexanol, octanol, and decanol.
[0077] Similarly, examples of the dihydric alcohol include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, cyclohexanediol, butanediol, pentanediol, hexanediol, trimethylene glycol, catechol, resorcinol, and hydroquinone.
[0078] Similarly, examples of the trihydric alcohol include glycerin, trimethylolpropane, trimethylolethane, butanetriol, and pentanetriol.
[0079] Similarly, examples of tetrahydric alcohols include pentaerythritol, diglycerin, sorbitan, and mannitan.
[0080] Similarly, examples of the pentahydric alcohol include arabic acid, examples of the hexahydric alcohol include tetraglycerin, sorbitol, and mannitol, and examples of the octahydric alcohol include sucrose.
[0081] These monohydric to octahydric alcohols also include partial esters obtained by partially esterifying polyglycerin, etc.
[0082] Examples of fatty acid diamides include ethylene bisstearylamide, ethylene bispalmitylamide, ethylene bismyristylamide, ethylene bislaurylamide, ethylene bisoleylamide, propylene bisstearylamide, propylene bispalmitylamide, propylene bismyristylamide, propylene bislaurylamide, propylene bisoleylamide, butylene bisstearylamide, butylene bispalmitylamide, butylene bismyristylamide, butylene bislaurylamide, butylene bisoleylamide, methylene bislaurylamide, methylene bisstearylamide, and hexamethylene bisstearylamide.
[0083] Examples of fatty acid monoamides include N-stearylstearylamide, oleic acid amide, erucic acid amide, and stearylamide.
[0084] <Fatty alcohol> The aliphatic alcohol as component (B) is not particularly limited, but examples thereof include alcohols having an alkyl chain with 4 to 22 carbon atoms, preferably monohydric alcohols having an alkyl chain with 4 to 22 carbon atoms. The alkyl chain may be either linear or branched, or may be a mixture of linear and branched chains. These aliphatic alcohols may be used alone or in combination of two or more. From the viewpoint of defoaming properties, the number of carbon atoms in the alkyl chain of the alcohol is preferably 6 to 22, more preferably 10 to 22, and even more preferably 12 to 18.
[0085] <Commercially available products> As component (B), commercially available products can be used, and examples of commercially available products include fatty acid derivatives such as DEFOMAX (registered trademark) 520, 702, and 1080 manufactured by Toho Chemical Industry Co., Ltd., and RIKEMAL (registered trademark) S-100, S-100P, S-100A, and H-100 manufactured by Riken Vitamin Co., Ltd., and aliphatic alcohols such as KALCOL (registered trademark) 6870 manufactured by Kao Corporation. Among these, KALCOL (registered trademark) 6870 manufactured by Kao Corporation and RIKEMAL (registered trademark) S-100A manufactured by Riken Vitamin Co., Ltd. are preferred from the viewpoint of easy availability.
[0086] [Method of producing particles] The particles of the present invention can be produced by any method as long as it can obtain particles having the above-mentioned particle diameter. However, it is preferable to use a suspension polymerization method from the viewpoints that the heat generated by polymerization can be easily controlled and impurities can be removed by washing the particles. The particles of the present invention can be produced, for example, by making a predetermined amount of component (B) present in the polymerization system in the production method of the (meth)acrylic copolymer (A) described below.
[0087] [Method for producing (meth)acrylic copolymer (A)] The (meth)acrylic copolymer (A) according to the present invention can be produced by a living polymerization method or a method using a macromonomer (a1) described below. In the process of producing the (meth)acrylic copolymer (A), the particles of the present invention can be produced by making the component (B) present in the polymerization reaction system.
[0088] Examples of the living polymerization method include a living radical polymerization method and a living anionic polymerization method. Examples of the living radical polymerization method include reversible addition-fragmentation chain transfer polymerization (RAFT), atom transfer radical polymerization (ATRP), nitroxide-mediated polymerization (NMP), and living radical polymerization with organic tellurium as a growth terminal (TERP). The method using the macromonomer (a1) is advantageous in that the (meth)acrylic copolymer (A) can be produced relatively easily, and is preferable because it has the advantage that it does not require the removal of catalyst or auxiliary residues or terminal treatment steps required in the living polymerization method.
[0089] [Method for producing (meth)acrylic copolymer (A) using macromonomer] In the method for producing the (meth)acrylic copolymer (A) using a macromonomer, the macromonomer may be used as a raw material for either the polymer (A1) or the polymer (A2). The macromonomer is copolymerized with a comonomer copolymerizable with the macromonomer to obtain a macromonomer copolymer. This macromonomer copolymer is used as the (meth)acrylic copolymer (A). Here, as an example, a method is described in which macromonomer (a1) is used as a raw material for polymer (A1), and macromonomer (a1) is copolymerized with monomer (a2) to produce a macromonomer copolymer. In this case, polymer (A2) has monomer (a2) as a monomer unit.
[0090] [Method for producing macromonomer (a1)] The macromonomer (a1) can be produced by a known method. Examples of the method for producing the macromonomer include a method using a cobalt chain transfer agent (US Pat. No. 4,680,352), a method using an α-substituted unsaturated compound such as α-bromomethylstyrene as a chain transfer agent (WO 88 / 04304), a method of chemically bonding a polymerizable group (JP-A-60-133007, US Pat. No. 5,147,952, JP-A-06-298921), and a method by thermal decomposition (JP-A-11-240854). Among these, the method for producing the macromonomer (a1) is preferably a method using a cobalt chain transfer agent, in that it has a small number of production steps and uses a catalyst with a high chain transfer constant.
[0091] Examples of the method for producing the macromonomer (a1) using a cobalt chain transfer agent include bulk polymerization, solution polymerization, and aqueous dispersion polymerization such as suspension polymerization, emulsion polymerization, etc. Among these, the aqueous dispersion polymerization is preferred from the viewpoint of simplifying the recovery process of the macromonomer (a1).
[0092] The cobalt chain transfer agent used in the present invention may be a cobalt chain transfer agent represented by the following general formula (2). For example, those described in Japanese Patent No. 3,587,530, JP-A-6-23209, JP-A-7-35411, U.S. Pat. Nos. 45,269,945, 4,694,054, 4,834,326, 4,886,861, 5,324,879, WO 95 / 17435, and JP-T-9-510499 may be used.
[0093] [ka]
[0094] [In the formula, R 11 ~R 14 are each independently an alkyl group, a cycloalkyl group, or an aryl group. 11 ~X 14 are each independently an F atom, a Cl atom, a Br atom, an OH group, an alkoxy group, an aryloxy group, an alkyl group, or an aryl group.
[0095] Specific examples of cobalt chain transfer agents include bis(boron difluorodimethyldioximinocyclohexane)cobalt(II), bis(boron difluorodimethylglyoximate)cobalt(II), bis(boron difluorodiphenylglyoximate)cobalt(II), cobalt(II) complexes of vicinaliminohydroxyimino compounds, cobalt(II) complexes of tetraazatetraalkylcyclotetradecatetraenes, N,N'-bis(salicylidene)ethylenediaminocobalt(II) complexes, cobalt(II) complexes of dialkyldiazadioxodialkyldodecadienes, and cobalt(II) porphyrin complexes. Among these, bis(boron difluorodiphenylglyoximate)cobalt(II)(R 11 ~R 14 : Phenyl group, X 11 ~X 14: F atom) is preferred. One or more of these can be appropriately selected and used.
[0096] The amount of the cobalt chain transfer agent used is preferably 5 ppm to 350 ppm based on 100 parts by mass of the monomer for obtaining the macromonomer (a1). If the amount of the cobalt chain transfer agent used is 5 ppm or more, the molecular weight is likely to be sufficiently reduced, and if it is 350 ppm or less, the obtained macromonomer (a1) is unlikely to be colored.
[0097] Examples of the solvent used when obtaining the macromonomer (a1) by solution polymerization include hydrocarbons such as toluene, ethers such as diethyl ether and tetrahydrofuran, halogenated hydrocarbons such as dichloromethane and chloroform, ketones such as acetone, alcohols such as methanol, nitriles such as acetonitrile, vinyl esters such as ethyl acetate, carbonates such as ethylene carbonate, and supercritical carbon dioxide. These can be used alone or in combination of two or more kinds.
[0098] [Method of manufacturing macromonomer copolymer] The method for producing the macromonomer copolymer includes a step of polymerizing a polymerizable mixture containing a polymerizable composition (X) and a polymerization initiator, which will be described later. In order to produce the particles of the present invention, in this polymerization reaction step, a polymerizable mixture containing the polymerizable composition (X), the polymerization initiator, and the aforementioned component (B) is used, and the polymerizable composition (X) is polymerized in the presence of component (B).
[0099] The polymerizable composition (X) contains a macromonomer (a1) and a comonomer copolymerizable with the macromonomer (a1). The comonomer is appropriately selected from the monomers (a2) that are copolymerizable with the macromonomer (a1). In particular, it is preferable to use the macromonomer (a1) represented by the following general formula (1).
[0100] [ka]
[0101] (In formula (1), R 0 ~R n are each independently a hydrogen atom, an alkyl group, a cycloalkyl group, an aryl group, or a heterocyclic group. 1 ~X n are each independently a hydrogen atom or a methyl group. Z is a terminal group. n is a natural number from 1 to 10,000.
[0102] <R 0 ~R n > In the formula (1), R 0 ~R n The alkyl group, cycloalkyl group, aryl group or heterocyclic group may have a substituent.
[0103] R 0 ~R n Examples of the alkyl group include branched or linear alkyl groups having 1 to 20 carbon atoms. Specific examples include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, and icosyl. Among these, in terms of availability, methyl, ethyl, n-propyl, i-propyl, n-butyl, t-butyl, pentyl, hexyl, heptyl, and octyl are preferred, methyl, ethyl, n-propyl, i-propyl, n-butyl, and t-butyl are more preferred, and methyl is particularly preferred.
[0104] R 0 ~R nExamples of the cycloalkyl group include cycloalkyl groups having 3 to 20 carbon atoms. Specific examples include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a t-butylcyclohexyl group, an isobornyl group, an adamantyl group, etc. From the viewpoint of availability, a cyclopropyl group, a cyclobutyl group, and an adamantyl group are preferred.
[0105] R 0 ~R n The aryl group may, for example, be an aryl group having a carbon number of 6 to 18. Specific examples include a phenyl group, a benzyl group, and a naphthyl group.
[0106] R 0 ~R n Examples of the heterocyclic group include heterocyclic groups having 5 to 18 carbon atoms. Specific examples include a γ-lactone group, an ε-caprolactone group, a morpholine group, etc. Examples of the heteroatom contained in the heterocycle include an oxygen atom, a nitrogen atom, a sulfur atom, etc.
[0107] R 0 ~R n The substituents of each independently include a group or atom selected from the group consisting of an alkyl group, an aryl group, a carboxy group, an alkoxycarbonyl group (-COOR'), a carbamoyl group (-CONR'R''), a cyano group, a hydroxy group, an amino group, an amide group (-NR'R''), a halogen atom, an allyl group, an epoxy group, an alkoxy group (-OR'), and a group exhibiting hydrophilicity or ionicity. Examples of R' and R'' each independently include R 0 ~R n and the like (excluding heterocyclic groups).
[0108] R 0 ~R n The alkoxycarbonyl group as the substituent of the above-mentioned formula (I) includes, for example, a methoxycarbonyl group. R 0 ~R nExamples of the carbamoyl group as a substituent of include an N-methylcarbamoyl group and an N,N-dimethylcarbamoyl group. R 0 ~R n The amide group as the substituent of the formula (I) includes, for example, a dimethylamide group. R 0 ~R n Examples of the halogen atom as a substituent of include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. R 0 ~R n The alkoxy group as the substituent includes, for example, an alkoxy group having a carbon number of 1 to 12. A specific example is a methoxy group. R 0 ~R n Examples of the hydrophilic or ionic group as the substituent of the formula (I) include an alkali salt of a carboxy group or an alkali salt of a sulfoxyl group, a poly(alkylene oxide) group such as a polyethylene oxide group or a polypropylene oxide group, and a cationic substituent such as a quaternary ammonium base.
[0109] R 0 ~R n is preferably at least one selected from an alkyl group and a cycloalkyl group, and more preferably an alkyl group. The alkyl group is preferably a methyl group, an ethyl group, an n-propyl group or an i-propyl group, and from the viewpoint of availability, a methyl group is more preferable.
[0110] <X 1 ~X n > In the formula (1), X 1 ~X n From the viewpoint of ease of synthesis of the macromonomer (a1), X 1 ~X n It is preferable that 80 mol % or more of the total number of moles of the above be methyl groups, relative to 100 mol %.
[0111] <z> In the formula (1), Z is a terminal group of the macromonomer (a1). Examples of the terminal group of the macromonomer (a1) include a hydrogen atom and a group derived from a radical polymerization initiator, similar to the terminal groups of polymers obtained by known radical polymerization.
[0112] The lower limit of the content of the methyl methacrylate unit contained in the macromonomer (a1) is not particularly limited, and if it is 50% by mass or more with respect to 100% by mass of the total mass of the macromonomer (a1), it is advantageous for improving impact resistance and transparency. The lower limit of the content of the methyl methacrylate unit is preferably 50% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. On the other hand, the upper limit of the content of the methyl methacrylate unit is not particularly limited, and may be 100% by mass of the methyl methacrylate unit, or may be 99% by mass or less with respect to 100% by mass of the total mass of the macromonomer (a1).
[0113] In the method for producing the macromonomer copolymer, the polymerization reaction is preferably carried out by using a radical polymerization method.
[0114] In the method for producing a macromonomer copolymer according to the present invention, the upper limit of the content of the sulfur-containing chain transfer agent contained in the polymerizable mixture is preferably less than 0.01 parts by mass relative to 100 parts by mass of the polymerizable composition (X). If the upper limit of the content of the sulfur-containing chain transfer agent is less than 0.01 parts by mass, the composition distribution of the copolymer can be prevented from becoming broad, so that the impact resistance of the obtained molded product can be improved. The lower limit of the content of the sulfur-containing chain transfer agent is not particularly limited, and it is more preferable that no sulfur-containing chain transfer agent is contained. The sulfur-containing chain transfer agent refers to a mercaptan compound such as n-butyl mercaptan or n-octyl mercaptan, which is added as a chain transfer agent in order to adjust the molecular weight of the copolymer during polymerization.
[0115] In the production of the macromonomer copolymer, the macromonomer can be polymerized so that the mass average molecular weight (Mw) of the obtained macromonomer copolymer is 100,000 or more and 2,500,000 or less. The lower limit of the mass average molecular weight (Mw) of the macromonomer copolymer is preferably 300,000 or more, more preferably 500,000 or more. On the other hand, the upper limit of the Mw of the macromonomer polymer is preferably 2,000,000 or less, more preferably 1,800,000 or less. If the mass average molecular weight (Mw) of the macromonomer copolymer is 100,000 or more, the flexibility and impact resistance of the molding material and molded body using the particles of the present invention are good. If the mass average molecular weight (Mw) of the macromonomer copolymer is 2,500,000 or less, the transparency and moldability of the molding material and molded body using the particles of the present invention are good. The above upper and lower limits can be combined arbitrarily. The method for controlling the mass average molecular weight (Mw) of the macromonomer copolymer within the above range is not particularly limited, and a person skilled in the art can control it by adjusting the polymerization method, the type and amount of polymerization initiator, the amount of chain transfer agent, the polymerization temperature, etc., according to well-known techniques.
[0116] [Polymerizable composition (X)] The polymerizable composition (X) is one of the raw materials of the (meth)acrylic copolymer (A). The content ratio (a1, unit: mass%) of the macromonomer (a1) and the content ratio (a2, unit: mass%) of the monomer (a2) contained in the polymerizable composition (X) are preferably a1:a2=35-75 mass%:65-25 mass%, more preferably a1:a2=40-70 mass%:60-30 mass%, further preferably a1:a2=45-70 mass%:55-30 mass%, particularly preferably a1:a2=50-65:50-35 mass%, and most preferably a1:a2=55-65:45-35 mass%, based on the total mass of the polymerizable composition (X) being 100 mass%. The content ratio (a1, unit: mass%) of the macromonomer (a1) and the content ratio (a2, unit: mass%) of the monomer (a2) contained in the polymerizable composition (X) are preferably a1:a2=35:65-75:25, more preferably a1:a2=40:60-70:30, still more preferably a1:a2=45:55-70:30 mass%, particularly preferably a1:a2=50:50-65:35, and most preferably a1:a2=55:45-65:35 mass%. If the lower limit of the content ratio of the macromonomer (a1) contained in the polymerizable composition (X) is 35 mass% or more, or the upper limit of the content ratio of the monomer (a2) is 65 mass% or less, relative to 100 mass% of the total mass of the polymerizable composition (X), the macromonomer copolymer has good handleability. In addition, when the lower limit of the content of the monomer (a2) contained in the polymerizable composition (X) is 25 mass% or more, or the upper limit of the content of the macromonomer (a1) is 75 mass% or less, relative to 100 mass% of the total mass of the polymerizable composition (X), the impact resistance of the molding material containing the macromonomer copolymer and the obtained molded article can be well maintained.
[0117] For convenience of explanation, the polymerizable composition (X) containing the macromonomer (a1) and the monomer (a2) is referred to as the "polymerizable composition (X)". However, it is not necessary to previously mix the macromonomer (a1) and the monomer (a2) to prepare the polymerizable composition (X). It is sufficient that the polymerizable composition (X) is in a state in which the macromonomer (a1) and the monomer (a2) coexist in the polymerization step.
[0118] [Production of macromonomer copolymers by suspension polymerization] The case where the polymerization reaction is carried out by the suspension polymerization method will be described in detail below. In the method for producing the macromonomer copolymer, when the macromonomer copolymer is produced by suspension polymerization, examples of the method include a method in which the production of the macromonomer (a1) of the present invention and the production of the macromonomer copolymer are carried out separately, which include the following steps i) to v), and a method in which the production of the macromonomer (a1) of the present invention and the production of the macromonomer copolymer of the present invention are carried out continuously, which includes the following steps I) to II) instead of the following i) to ii) of the following steps i) to v).
[0119] i) Syrup preparation process The bead-like macromonomer (a1) produced by suspension polymerization is dissolved in a solution containing the monomer (a2) to prepare a syrup, which is designated as the polymerizable composition (X). When preparing the polymerizable composition (X), a mixture containing the macromonomer (a1) and the monomer (a2) can be heated at a temperature equal to or lower than the boiling point of the monomer (a2) to promote dissolution of the macromonomer (a1). The temperature at which the polymerizable composition (X) is prepared is preferably in the range of 20°C to 100°C, more preferably in the range of 40°C to 80°C. When the radical polymerization initiator used does not react at the temperature at which the polymerizable composition (X) is prepared, the radical polymerization initiator can be mixed with the polymerizable composition (X) to obtain a polymerizable mixture, and then the polymerizable mixture can be heated.
[0120] ii) Radical polymerization initiator dissolving step In the case where the radical polymerization initiator reacts at the temperature for preparing the polymerizable composition (X) obtained in the step i), the polymerizable composition (X) is once cooled to room temperature or below, and then the radical polymerization initiator is added and dissolved uniformly to obtain a polymerizable mixture. The temperature of the polymerizable composition (X) when the radical polymerization initiator is added is preferably a temperature equal to or lower than the 10-hour half-life temperature of the radical polymerization initiator minus 15°C. The component (B) may be added to this polymerizable mixture or may be added to the aqueous solution described below.
[0121] iii) Preparation of an aqueous solution The polymerizable mixture and the aqueous solution are mixed and then stirred to prepare a suspension in which droplets of the polymerizable mixture are dispersed in the aqueous solution. The aqueous solution is an aqueous solution for dispersing the polymerizable mixture, and may contain a dispersant, an electrolyte, component (B), and other auxiliaries. By appropriately selecting a combination of a dispersant and an electrolyte, the dispersibility of droplets of the polymerizable mixture formed in the aqueous solution when the polymerizable mixture is dispersed in the aqueous solution can be controlled. The water used in the aqueous solution is preferably deionized water, since this improves the dispersibility of the droplets of the polymerizable mixture.
[0122] Examples of the dispersant include an alkali metal salt of poly(meth)acrylic acid, a copolymer of an alkali metal salt of (meth)acrylic acid and a (meth)acrylic acid ester, a copolymer of an alkali metal salt of a sulfoalkyl (meth)acrylate and a (meth)acrylic acid ester, an alkali metal salt of polystyrenesulfonic acid, a copolymer of an alkali metal salt of styrenesulfonic acid and a (meth)acrylic acid ester, or a copolymer consisting of a combination of these monomers; polyvinyl alcohol having a saponification degree of 70 to 100%, methyl cellulose, starch, and hydroxyapatite. These can be used alone or in combination of two or more kinds. Among these, a copolymer of an alkali metal salt of a sulfoalkyl (meth)acrylate and a (meth)acrylic acid ester and a copolymer of an alkali metal salt of (meth)acrylic acid and a (meth)acrylic acid ester, which have good dispersion stability during suspension polymerization, are preferred. The amount of the dispersant to be added is, for example, in the range of 0.0005 to 0.5 parts by mass relative to 100 parts by mass of the polymerizable composition (X). Examples of the electrolyte include sodium carbonate, sodium sulfate, manganese sulfate, etc. The amount of the electrolyte added is, for example, in the range of 0.01 to 1.0 part by mass with respect to 100 parts by mass of the polymerizable composition (X).
[0123] I) Syrup preparation process The polymerizable composition (X) is prepared by adding a solution containing a monomer (a2) to a bead-like macromonomer (a1) produced by suspension polymerization dispersed in an aqueous solution. The temperature at which the macromonomer (a1) is dissolved in the solution containing the monomer (a2) is preferably in the range of 20°C to 100°C, more preferably in the range of 40°C to 90°C, and further preferably in the range of 50°C to 80°C.
[0124] II) Radical polymerization initiator dissolution process In the case where the radical polymerization initiator reacts at the temperature for preparing the polymerizable composition (X) obtained in the step I), the polymerizable composition (X) is once cooled to room temperature or below, and then the radical polymerization initiator and component (B) are added and dissolved uniformly to obtain a polymerizable mixture. The temperature of the polymerizable composition (X) when the radical polymerization initiator is added is preferably a temperature equal to or lower than the 10-hour half-life temperature of the radical polymerization initiator minus 15°C.
[0125] When the polymerization reaction is carried out in the presence of a radical polymerization initiator, the radical polymerization initiator can be a known organic peroxide such as 2,4-dichlorobenzoyl peroxide or t-butyl peroxypivalate, or a known azo compound such as 2,2'-azobisisobutyronitrile or 2,2'-azobis(2,4-dimethylvaleronitrile). The amount of the radical polymerization initiator to be added can be appropriately selected by a person skilled in the art according to well-known techniques. The usual amount of the radical polymerization initiator to be added is 0.0001 to 10 parts by mass per 100 parts by mass of the total amount of the polymerizable composition (X).
[0126] iv) Polymerization reaction process The obtained suspension is then heated while being stirred to initiate the polymerization reaction. It is preferable to remove dissolved oxygen by subjecting the polymerizable mixture and the aqueous solution before heating to degassing under reduced pressure or nitrogen replacement. The polymerization temperature during the polymerization reaction is an important condition for obtaining a macromonomer copolymer in high yield. The polymerization temperature here refers to the temperature of the suspension. The polymerization temperature is preferably 50°C to 90°C, more preferably 60°C to 85°C, and even more preferably 65°C to 80°C. If the polymerization temperature is too low, there is a concern that the reaction will proceed slowly and the polymerization time will be long. Also, if the polymerization temperature is too high, the cleavage of the adduct radical, which is a reaction intermediate, takes precedence, and the yield of the macromonomer copolymer tends to decrease. In the latter stage of the polymerization reaction, the suspension can be heated to increase the reaction rate of the polymerizable composition (X) and to eliminate the unreacted radical polymerization initiator. The temperature at which the suspension is heated is preferably 80° C. or higher, more preferably 85° C. or higher. The temperature rise time may be determined by calculating the time required for the radical polymerization initiator to disappear, and is usually about 30 minutes to 2 hours.
[0127] v) Recovery process After the above steps, the suspension is cooled to room temperature or below, and the resulting bead-like copolymer is recovered by a known method such as filtration. If necessary, a washing step for removing impurities such as dispersants and electrolytes, a step for removing beads containing air bubbles, a drying step, etc. may be performed. The finally obtained bead-like macromonomer copolymer is the particle of the present invention.
[0128] [Amount of component (B) added] In the above-mentioned method for producing particles of the present invention, the amount of component (B) added to the polymerization system may be any amount that enables the production of particles of the present invention containing component (B) in the above-mentioned suitable content, for example, as follows. That is, in the production of the particles of the present invention, the amount of component (B) added is not particularly limited, but is preferably 0.0001 parts by mass or more and 0.5 parts by mass or less relative to 100 parts by mass of the polymerizable composition (X). The lower limit of the amount of component (B) added is more preferably 0.0005 parts by mass or more relative to 100 parts by mass of the polymerizable composition (X), more preferably 0.001 parts by mass, and particularly preferably 0.002 parts by mass. The upper limit of the amount of component (B) added is more preferably 0.35 parts by mass, and more preferably 0.2 parts by mass relative to 100 parts by mass of the polymerizable composition (X). When the amount of component (B) added is 0.0001 parts by mass or more relative to 100 parts by mass of polymerizable composition (X), the particles of the present invention have a small particle size, and molding materials and molded articles using the particles can exhibit excellent releasability and appearance. When the amount of component (B) added is 0.5 parts by mass or less relative to 100 parts by mass of polymerizable composition (X), the yield of the particles of the present invention is increased, and productivity is improved.
[0129] In the production of the particles of the present invention, the component (B) added to the polymerization system has a structure that has both hydrophobic and hydrophilic properties, and therefore can move between oil droplets and the aqueous system. For example, in suspension polymerization, a portion of the charged amount becomes contained in the particles of the (meth)acrylic copolymer (A).
[0130] [Application] The particles of the present invention have a small particle diameter and a low content of coarse particles, and therefore have excellent uniform dispersion and kneadability in matrix materials, and can be effectively used in a wide range of applications, such as paint raw materials; additives for ink adhesives, adhesives, artificial marble, etc.; fillers for paper processing materials, cosmetics, etc.; column fillers for chromatography; additives for toners used in electrostatic image development; anti-blocking agents for films; and light diffusing agents. They are particularly useful as modifiers for improving the impact resistance of acrylic resins. EXAMPLES
[0131] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following, "parts" means "parts by mass".
[0132] The evaluations in the examples and comparative examples were carried out by the following methods.
[0133] (Mass average molecular weight (Mw) and number average molecular weight (Mn) of macromonomer (a1)) The mass average molecular weight (Mw) and number average molecular weight (Mn) of the macromonomer (a1) obtained in the examples and comparative examples were measured by gel permeation chromatography (GPC). 10 mg of the obtained copolymer was dissolved in 10 mL of tetrahydrofuran, and the solution was filtered through a 0.45 μm filter to prepare a sample for GPC measurement. A polymer measurement guard column (manufactured by Tosoh Corporation, product name: TSK-GUARD COLUMN SUPER HH) and two polymer measurement columns (manufactured by Tosoh Corporation, product name: TSK-GEL SUPER HM-H) were connected in series to a gel permeation chromatography measurement device (manufactured by Tosoh Corporation, model name: HLC-8320). A differential refractometer (RI) was used as the detector. Measurements were performed under the following conditions: separation column temperature: 40°C, mobile phase: tetrahydrofuran, mobile phase flow rate: 0.6 mL / min, sample injection volume: 10 μL. A calibration curve was created using several types of polymethyl methacrylate with known molecular weights (Polymer Laboratories, peak molecular weight (Mp) 1,560 to 19,500,000) as standard polymers, and Mw and Mn were determined.
[0134] (Mass average molecular weight (Mw) and number average molecular weight (Mn) of macromonomer copolymer) The mass average molecular weight (Mw) and number average molecular weight (Mn) of the macromonomer copolymer, which is the (meth)acrylic copolymer (A) obtained in the examples and comparative examples, were measured using gel permeation chromatography (GPC). 10 mg of the obtained copolymer was dissolved in 10 mL of tetrahydrofuran, and the solution filtered through a 0.45 μm filter was used as a sample for GPC measurement. In the GPC measurement of the copolymer, a high-performance liquid chromatography measurement device (manufactured by Tosoh Corporation, model name: HLC-8320 type) was used in series with a polymer measurement guard column (manufactured by Tosoh Corporation, product name: TSK-GUARD COLUMN SUPER HH) and one super polymer measurement column (manufactured by Tosoh Corporation, product name: TSK-GEL GMHHR-H). A differential refractometer (RI) was used as the detector. Measurements were performed under the following conditions: separation column temperature: 40°C, mobile phase: tetrahydrofuran, mobile phase flow rate: 0.6 mL / min, sample injection volume: 10 μL. A calibration curve was created using several types of polymethyl methacrylate with known molecular weights (Polymer Laboratories, peak molecular weight (Mp) 1,560 to 19,500,000) as standard polymers, and the mass average molecular weight (Mw) and number average molecular weight (Mn), which are relative molecular weights converted to polymethyl methacrylate, were determined.
[0135] (Particle classification) Particle classification was performed using an all-stainless steel test sieve (φ75×20H, #12 mesh, 1.4 mm opening, compliant with JIS Z8801-1) manufactured by Nonaka Rikaki Seisakusho Co., Ltd. Large particles remaining on the test sieve were classified as coarse particles or #12 mesh ON, and particles that passed through the test sieve were classified as #12 mesh PASS.
[0136] (Volume average particle size) The volume average particle size of the obtained particles was measured using a laser diffraction / scattering type particle size distribution analyzer LA-960S manufactured by HORIBA Ltd. The measurement was carried out by placing the sample in approximately 180 mL of ion-exchanged water, which was the dispersion medium, so that the semiconductor laser transmittance was 90-80% and the LED transmittance was 90-70%.
[0137] (raw materials) The abbreviations for the compounds used in the examples and comparative examples are as follows. MMA: Methyl methacrylate (Mitsubishi Chemical) MA: Methyl acrylate (Mitsubishi Chemical) BA: n-butyl acrylate (Mitsubishi Chemical) ST: Styrene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Dispersant (1): Dispersant prepared in Production Example 1 Chain transfer agent (1): Chain transfer catalyst prepared in Preparation Example 2 Polymerization initiator (1): 1,1,3,3-tetramethylbutylperoxy 2-ethylhexanoate (manufactured by NOF Corporation, trade name: Perocta O) Polymerization initiator (2): 2,2'-azobis(2-methylbutyronitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product name: V-59) Ingredient (B): Cetyl alcohol (a fatty alcohol with an alkyl chain containing 16 carbon atoms, manufactured by Kao Corporation, product name: Kalcol (registered trademark) 6870) Glycerol monostearate: (fatty acid ester derived from glycerol, a trihydric alcohol having an alkyl group with 3 carbon atoms, and stearic acid, a carboxylic acid having an alkyl chain with 17 carbon atoms; manufactured by Riken Vitamin Co., Ltd.; product name: Rikemal (registered trademark) S-100A)
[0138] [Production Example 1: Synthesis of Dispersant (1)] In a reactor equipped with a stirrer, a cooling tube and a thermometer, 61.6 parts of 17% by mass potassium hydroxide aqueous solution, 19.1 parts of MMA and 19.3 parts of deionized water were charged. Next, the liquid in the reactor was stirred at room temperature, and after confirming the exothermic peak, the mixture was stirred for 4 hours. After this, the reaction liquid in the reactor was cooled to room temperature to obtain an aqueous potassium methacrylate solution.
[0139] Next, 900 parts of deionized water, 70 parts of 42% by mass 2-sulfoethyl sodium methacrylate aqueous solution (manufactured by Mitsubishi Chemical Corporation, trade name: Acryester SEM-Na), 16 parts of the above potassium methacrylate aqueous solution, and 7 parts of MMA were added to a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, and the liquid in the reaction apparatus was heated to 50° C. while the inside of the polymerization apparatus was replaced with nitrogen. 0.053 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 2,2'-azobis(2-methylpropionamidine) dihydrochloride, trade name) was added as a polymerization initiator to the polymerization apparatus, and the liquid in the reaction apparatus was heated to 60° C. After the polymerization initiator was added, 1.4 parts of MMA was added in portions every 15 minutes for a total of 5 times (total amount of MMA was 7 parts). Thereafter, the liquid in the polymerization apparatus was kept at 60° C. for 6 hours with stirring, and then cooled to room temperature to obtain a dispersant (1) having a solid content of 8 mass % as a transparent aqueous solution.
[0140] [Production Example 2: Synthesis of Chain Transfer Agent (1)] In a synthesis apparatus equipped with a stirrer, 2.00 g (8.03 mmol) of cobalt (II) acetate tetrahydrate (FUJIFILM Wako Pure Chemical Industries, Ltd., Wako special grade), 3.86 g (16.1 mmol) of diphenylglyoxime (Tokyo Chemical Industry Co., Ltd., EP grade), and 100 mL of diethyl ether that had been deoxygenated in advance by nitrogen bubbling were placed under a nitrogen atmosphere, and the mixture was stirred at room temperature for 2 hours.
[0141] Next, 20 mL of boron trifluoride diethyl ether complex (Tokyo Chemical Industry Co., Ltd., EP grade) was added and stirred for another 6 hours. The obtained product was filtered, and the solid was washed with diethyl ether and dried at 100 MPa or less at 20°C for 12 hours to obtain 5.02 g (7.93 mmol, yield 99% by mass) of a brown solid chain transfer agent (1).
[0142] [Production Example 3: Synthesis of Macromonomer (a1)] In a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, 145 parts of deionized water, 0.1 parts of sodium sulfate (Na2SO4), and 0.26 parts by mass of dispersant (1) (solid content 8 mass%) produced in Production Example 1 were added and stirred to obtain a uniform aqueous solution. Next, 95 parts of MMA, 5.0 parts of MA, 0.0014 parts of chain transfer agent (1) produced in Production Example 2, and 0.25 parts of polymerization initiator (1) were added to obtain an aqueous dispersion.
[0143] Next, the inside of the polymerization apparatus was thoroughly replaced with nitrogen, and the aqueous dispersion was heated to 80°C and held for 3 hours, then heated to 90°C and held for 2 hours. The reaction solution was then cooled to 40°C to obtain an aqueous suspension of a macromonomer. This aqueous suspension was filtered through a filter cloth, and the filtrate was washed with deionized water and dried at 40°C for 16 hours to obtain a bead-like macromonomer (a1). The obtained macromonomer (a1) had a number average molecular weight (Mn) of 21,300 and a mass average molecular weight (Mw) of 39,100.
[0144] [Example 1] In a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, 60.0 parts of the macromonomer (a1) obtained in Production Example 3, 145 parts of deionized water, 0.1 parts of dispersant (1), 0.1 parts of sodium sulfate, and 0.01 parts of Kalcol 6870 as component (B) were added and stirred to obtain an aqueous suspension. Next, the temperature inside the polymerization apparatus was raised to 70°C, and 33.2 parts of BA and 6.8 parts of ST were slowly added. Then, the mixture was stirred and held at 70°C for 1 hour to dissolve the macromonomer (a1) in BA and ST, and a dispersion was obtained. Next, the inside of the polymerization apparatus was cooled to 40°C, and 0.5 parts of polymerization initiator (2) was added and stirred for 30 minutes to dissolve. Next, the inside of the polymerization apparatus was fully replaced with nitrogen, and the aqueous dispersion was heated to 82°C and held for 4 hours, and then heated to 90°C and held for 1 hour. After cooling to 40°C or less, the mixture was filtered through a filter cloth, and the filtrate was washed with deionized water. The filtered product was then dried at 40°C for 12 hours using a hot air circulation dryer to obtain particles containing (meth)acrylic copolymer (A), which is a bead-shaped macromonomer copolymer. The obtained particles containing (meth)acrylic copolymer (A) had a number average molecular weight (Mn) of 62,600 and a mass average molecular weight (Mw) of 683,200. The obtained particles were classified using a #12 mesh (a sieve with an opening of 1.4 mm), and the particles that passed through the sieve were designated as #12 mesh PASS, and the particles remaining on the sieve were designated as #12 mesh ON. In the particles obtained in Example 1, the proportion of #12 mesh PASS was 85%, and the proportion of #12 mesh ON was 9%, when the mass of the solid content of the charge was taken as 100%. Among the particles that passed the #12 mesh, the volume average particle size of the particles that had settled in the aqueous dispersion after polymerization (settled particles) was 307 μm. The Tg of the homopolymer of styrene (ST) is 100°C (POLYMER HANDBOOK FOURTH EDITION 2003), and the Tg of the homopolymer of n-butyl acrylate (BA) is -54°C (POLYMER HANDBOOK FOURTH EDITION 2003). The Tg of the homopolymer of polymer (A2) contained in (meth)acrylic copolymer (A) was calculated to be -37.5°C using the Fox formula.
[0145] [Example 2] Particles of Example 2 were obtained in the same manner as in Example 1, except that the type of component (B) was changed as shown in Table 1. The obtained particles containing the (meth)acrylic copolymer (A) had a number average molecular weight (Mn) of 71,000 and a mass average molecular weight (Mw) of 1,248,400. Of the obtained particles, the proportion of #12 mesh pass was 58%, and the proportion of #12 mesh on was 36%, when the mass of the charged solid content was 100%. Among the particles that had passed the #12 mesh, the volume average particle size of the particles that had settled in the aqueous dispersion after polymerization was 489 μm.
[0146] [Comparative Example 1] Except for not using the component (B), particles of Comparative Example 1 were obtained in the same manner as in Example 1. The obtained (meth)acrylic copolymer (A) particles had a number average molecular weight (Mn) of 62,600 and a mass average molecular weight (Mw) of 777,100. Of the obtained particles, the proportion of #12 mesh pass was 57%, and the proportion of #12 mesh on was 41%, when the mass of the charged solid content was 100%. Among the particles that had passed the #12 mesh, the volume average particle size of the particles that had settled in the aqueous dispersion after polymerization was 723 μm.
[0147] [Table 1]
[0148] Comparing the particles obtained in Examples 1 and 2 with those obtained in Comparative Example 1, it was found that the volume average particle size of the particles was reduced by adding component (B). This is believed to be because component (B) improved the affinity between the oil droplets and the water system during suspension polymerization, and activated the coalescence and redispersion of the oil droplets. In addition, it was found from Example 1 that when the aliphatic alcohol Rikemal 6870 was used as component (B), the proportion of #12 mesh ON in particular could be significantly reduced, and the volume average particle size of the obtained particles could also be reduced.< / z>
Claims
1. A particle comprising a (meth)acrylic copolymer (A) and a component (B), The (meth)acrylic copolymer (A) is a block copolymer and / or a graft copolymer, The particle, wherein the component (B) is at least one selected from a fatty acid, a fatty acid derivative, and an aliphatic alcohol.
2. The particle according to claim 1 , wherein the component (B) has an alkyl chain having 12 to 18 carbon atoms.
3. The particle of claim 1 , wherein the component (B) comprises an aliphatic alcohol.
4. The particle according to claim 1 , wherein the content of the component (B) is 0.0001 parts by mass or more and 0.5 parts by mass or less based on 100 parts by mass of the (meth)acrylic copolymer (A).
5. The particle according to claim 1 , wherein the (meth)acrylic copolymer (A) comprises a polymer (A1) containing 50 mass % or more of repeating units derived from methyl methacrylate in the polymer molecule.
6. The particles according to claim 1 , wherein the volume average particle size of the particles is 30 μm or more and 600 μm or less.
7. 2. The particles according to claim 1, wherein the proportion of coarse particles remaining on a sieve having an opening of 1,400 μm among the particles is 30 mass% or less.
8. The particle according to claim 5, wherein the (meth)acrylic copolymer (A) is a polymer containing the polymer (A1) and the polymer (A2) in a polymer molecule, and the polymer (A2) has a glass transition temperature (Tg) of 0°C or lower.
9. The particle according to claim 5 , wherein the (meth)acrylic copolymer (A) contains, as the polymer (A1), a structural unit derived from a macromonomer (a1) represented by the following general formula (1): 【Chemistry 1】 (In formula (1), R 0 ~R n are each independently a hydrogen atom, an alkyl group, a cycloalkyl group, an aryl group, or a heterocyclic group. 1 ~X n are each independently a hydrogen atom or a methyl group; Z is a terminal group; and n is a natural number from 1 to 10,000.
10. The particle according to claim 8, wherein the monomer unit constituting the polymer (A2) is a constituent unit derived from one or more monomers (a2) selected from the group consisting of methyl acrylate, ethyl acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tridecyl (meth)acrylate, i-stearyl (meth)acrylate, and styrene.
11. A method for producing particles, comprising a step of polymerizing a mixture containing a polymerizable composition (X), a component (B), and a polymerization initiator, the polymerizable composition (X) contains a macromonomer (a1) and a monomer (a2) copolymerizable with the macromonomer (a1); The method for producing particles, wherein the component (B) is at least one selected from the group consisting of fatty acids, fatty acid derivatives, and aliphatic alcohols.
12. The method for producing particles according to claim 11, wherein the particles have a volume average particle size of 30 μm or more and 600 μm or less.
13. The method for producing particles according to claim 11 , wherein the component (B) contains an alkyl chain having 12 to 18 carbon atoms.
14. The method for producing particles according to claim 11 , wherein the component (B) comprises an aliphatic alcohol.
15. The method for producing particles according to claim 11 , wherein the macromonomer (a1) is represented by the following formula (1): 【Chemistry 2】 (In formula (1), R 0 ~R n are each independently a hydrogen atom, an alkyl group, a cycloalkyl group, an aryl group, or a heterocyclic group. 1 ~X n are each independently a hydrogen atom or a methyl group; Z is a terminal group; and n is a natural number from 1 to 10,000.
16. The method for producing particles according to claim 15, wherein the monomer (a2) is at least one selected from the group consisting of methyl acrylate, ethyl acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tridecyl (meth)acrylate, i-stearyl (meth)acrylate, and styrene.
Citation Information
Patent Citations
Evacuation treatment device having conductor mounted thereto
JP1987021804A
Polymer particle and production method thereof
JP2007217645A
Resin particles and method for producing the same
JP2015193861A
Copolymer, resin composition, molded article, film-like molded article, and method for producing copolymer
JP2022065185A